Opportunities and challenges of conducting vaccine research in low and middle-income countries in the Asia–Pacific region: perspectives from the Asia–Pacific Vaccine Research Network - Jarir At Thobari; Eggi Arguni; Janis Asuncion Bunoan-Macazo; Stephanie Clark; Narangerel Dorj; Vannida Douangboupha; Pawinee Doungngern; Ha Hai Vu; Lukman Ade Chandra; Jonathan Hasian Haposan; Isireli Koroituku; Phonethipsavanh Nouanthong; et al. (The Lancet Regional Health. Western Pacific)
Summary: During the COVID-19 pandemic, vaccine technology and development advanced substantially in high-income countries, but this progress was not followed by the equitable knowledge transfer and accessibility and uptake of vaccines, particularly among low-and middle-income countries (LMICs). The Asia–Pacific Vaccine Research Network is a collaborative platform that aims to address common challenges faced by Asia–Pacific LMICs in undertaking vaccine research and barriers to evidence-based immunisation policy and practice. A network workshop was held in 2023 that aimed to identify critical challenges and opportunities to advance vaccine research to inform immunisation policy in LMICs in the Asia–Pacific. We found common themes to be challenges and opportunities in vaccine research capacity and infrastructure, workforce availability, financing and regulatory issues. To help to address some of these common challenges across the region, the Asia–Pacific Vaccine Research Network aims to facilitate the upskilling of vaccine research capability and knowledge exchange by bringing together experts and stakeholders from diverse backgrounds and through collaboration.